Influence of University Curriculum Design on Employability of Kenyan Graduates: Public Universities Perspective - Mwebia, Lilian; Kyuli, Kavitah C. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Despite the rising levels of education in Kenya, many graduates face very high unemployment rates. This raises questions on the demand and market orientation of the university curriculum design and whether the university course designers are cognizant of labor market trends. It for this reason this paper sought to investigate the influence of university curriculum design on employability of Kenyan graduates. A descriptive survey research design was applied in this study. The paper gathered feedback on the influence of university curriculum design on employability of Kenyan graduates from graduates and employers of Super Markets in Nakuru Town. Data was collected from one hundred and forty (130) graduates and (10 managers) employers of graduates about the proficiency of graduates in relation to each of the employability capabilities as a result of graduating from undergraduate programs. Both qualitative and quantitative data from the surveys was analyzed. A descriptive statistical analysis approach was used to analyze the quantitative data. The study found that experience as a highly required factor in the job market. The study also found that internships as very useful especially for graduates looking for their first opportunity in the world of work. The study also found that industrial attachment for lecturers was important as it was thought to help them gain the industry practices. The study concluded that the experiential learning approach should be deliberately designed around an open-ended authentic project and negotiated between university and industry stakeholders. This study recommends creation of employer voice on skills through establishment of a commission for employment and skills. The study also recommends increasing university investment in internship in degree and postgraduate programs and strong partnership with employers while designing curriculum.